2018
DOI: 10.1021/acsami.8b17495
|View full text |Cite
|
Sign up to set email alerts
|

Integrating 3D Printing and Biomimetic Mineralization for Personalized Enhanced Osteogenesis, Angiogenesis, and Osteointegration

Abstract: Titanium (Ti) alloy implants can repair bone defects at load-bearing sites. However, they mechanically mismatch with the natural bone and lack customized adaption with the irregularly major-sized load-bearing bone defects, resulting in the failure of implant fixation. Mineralized collagen (MC), a building block in bone, can induce angiogenesis and osteogenesis, and 3D printing technology can be employed to prepare scaffolds with an overall shape customized to the bone defect. Hence, we induced the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 37 publications
0
63
0
1
Order By: Relevance
“…Bone defects caused by trauma, infection, and tumour resection are common and seriously endanger bone healing [1][2][3][4]. Currently, porous titanium implants based on 3D printing have become a bone substitute because of their porous property and the open porous structure facilitates the transport of blood and nutrients in the implant, promoting tissue regeneration and reconstruction and speeds up the repair process [5][6][7][8][9][10]. However, the titanium surface has low bioactivity, forms a simple mechanical interlock with the bone tissue, and does not induce bone integration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone defects caused by trauma, infection, and tumour resection are common and seriously endanger bone healing [1][2][3][4]. Currently, porous titanium implants based on 3D printing have become a bone substitute because of their porous property and the open porous structure facilitates the transport of blood and nutrients in the implant, promoting tissue regeneration and reconstruction and speeds up the repair process [5][6][7][8][9][10]. However, the titanium surface has low bioactivity, forms a simple mechanical interlock with the bone tissue, and does not induce bone integration.…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic bone grafts have the risks of immune diseases and of slowing bone remodelling [1][2][3]. 3D-printed porous titanium (3D PPT) is a potential bone substitute material because of its porous structure simulating natural bone, which is beneficial to the growth of new bone tissue and provides a new way to treat bone defects [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, young adults were selected, facilitating and standardizing the time of achieving CSD. A longer evaluation time was not established in our study, however, based on the results of other studies, which was observed bone consolidation in CSD filled with biomaterials and cells, it may be suggested that the period of assessment was adequate (GEIGER et al, 2007;KASTEN et al, 2008;PEARCE et al, 2007) CSD models have been performed in femur, rib, tibia, mandible and radius with great efficacy (CARLISLE et al, 2019;CLOUGH;MCCARLEY;GREGORY, 2015;LIU et al, 2016;MANASSERO et al, 2013;ZHAO et al, 2016). In rabbits a complete failure in diaphysis of radius can be performed and the ulna work as a bridge, stabilizing the fracture and avoiding the use of implants.…”
Section: Resultsmentioning
confidence: 61%
“…Several studies have shown that using a radial ostectomy without cutting the ulna allows early and full limb function in rabbits, which is remarkably desirable (GEIGER et al, 2007;NIEMEYER et al, 2010;ZHAO et al, 2016). The bone region may vary between diaphyseal or metaphyseal, being the first one most commonly used to perform critical size defects in rabbits (CSD) (MA et al, 2018;WANG et al, 2019;XIE et al, 2017;ZHANG et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of bone defects, especially segmental large defects, 3D scaffolds can be biodegraded under the condition of persistent body load to match the formation of new bone tissue [ 175 , 176 ]. In addition, compared with other technologies, 3D scaffolds are able to deliver personalized, customized treatments [ 177 ]. The BP-based 3D printed scaffold integrates BP photothermal, osteogenesis and other natural advantages, making use of the good skeleton support of 3D scaffold, which will be better applied in segmental bone repair and treatment, and make up for the shortcomings of other existing materials such as insufficient mechanical properties.…”
Section: Application Of Bp-based 3d Printed Scaffold In Bone Regeneramentioning
confidence: 99%